IMPLEMENTASI STRATEGI PEMBELAJARAN SHEMAP DALAM MENINGKATKAN POLA PIKIR KRITIS DAN KREATIF PADA MAHASISWA S1 KEPERAWATAN DI STIKES dr. SOEBANDI - Andi Eka pranata (Jurnal Kesehatan dr. Soebandi, 2015)
The SHEMAP method is a learning method developed from the HOTS (Higher Order-Thinking Skills) concept which focuses on analytic thinking patterns, so students are required to analyze and explore ideas according to the mind maps created independently. The design of this study used a quasi experiment with a non equivalent control group design approach. The population in this study were 100 fourth semester students of STIKES Nursing Undergraduate Program dr. Soebandi Jember. The sample calculation in this study uses the Slovin formula. From the sample calculation above, the samples in this study were 80 fourth semester students of STIKES Nursing Undergraduate Program dr. Soebandi was divided into 2 groups, namely 40 students for the intervention group and 40 students for the control group. The sampling technique used in this study was cluster sampling, the time of research data collection began in July - August 2015. Changes Increased creative mindset in the control group by 77%, and increased creative mindset in the intervention group after the implementation of the SHEMAP method by 95% . From the results of the test analysis of the independent t test with a value of p = 0,000 (degrees α = 0.05), so that p <α (0,000 <0.05). This means that Ho is rejected or there is an influence of the SHEMAP learning method on improving creative thinking